A piggyBac transposon‐ and gateway‐enhanced system for efficient BAC transgenesis. Issue 9 (September 2014) - Zhao, Liang; Ng, Ee Ting; Koopman, Peter
<x xml:space="preserve">Abstract</x> Background : Bacterial artificial chromosomes (BACs) have become increasingly popular vectors for making transgenic mice, as they are able to carry large genomic DNA fragments that in many cases are needed to reproduce the endogenous gene expression pattern. However, the efficiency of BAC transgenesis is generally low, and gene transfer to BAC vectors by recombination‐mediated engineering (recombineering) is time‐consuming and technically demanding. Results and Conclusions: We present an enhanced system, comprising a BAC vector retrofitted with piggyBac DNA transposon elements and attL (Gateway) docking sites, that obviates these problems. Using this system, a gene‐of‐interest (such as a reporter gene) is transferred to the vector in a one‐step in vitro reaction, and piggyBac transposition mediates transgene integration at high efficiency when microinjected into mouse zygotes with piggyBac transposase mRNA. We establish proof‐of‐principle for this system using a Wilms tumour‐1 (Wt1) BAC to drive expression of an mCherry‐2A‐EGFP (RG) reporter gene, which yielded transgenic mice at a frequency of 33%, and recapitulated endogenous WT1 expression in developing gonads, kidneys and heart. The system we describe is applicable to any BAC transgenesis strategy. Developmental Dynamics 243:1086–1094, 2014. © 2014 Wiley Periodicals, Inc.